2016
DOI: 10.1016/j.msard.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of dietary salt intake in pediatric-onset multiple sclerosis

Abstract: Background High salt intake may be associated with pro-inflammatory changes in the immune response, and increased clinical and MRI activity in adults with relapsing-remitting multiple sclerosis. Objective We sought to determine if dietary salt intake is associated with pediatric-onset MS risk in a multicenter, case-control study. Methods Pediatric-onset CIS/MS cases within four years of onset and controls less than 22 years old recruited from 14 pediatric-MS centers were studied. Dietary sodium intake was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 23 publications
2
50
1
5
Order By: Relevance
“…The findings of Nourbakhsh et al are in the same direction with a previous report from the same group showing a lack of association between sodium intake and the risk of developing MS,9 but they contrast with the immunological findings and what we found in a Hispanic cohort of adult MS 8. Several factors could have accounted for divergent findings.…”
supporting
confidence: 79%
“…The findings of Nourbakhsh et al are in the same direction with a previous report from the same group showing a lack of association between sodium intake and the risk of developing MS,9 but they contrast with the immunological findings and what we found in a Hispanic cohort of adult MS 8. Several factors could have accounted for divergent findings.…”
supporting
confidence: 79%
“…Spot urine testing is affordable and practical although its use for estimating sodium intake has remained controversial. 13 Using the same cohort of patients and appropriate controls, we did not find any association of sodium intake and risk of developing paediatric MS. 14 Our study had 80% power to detect a modest increase of 60% in the hazard of relapse in patients with excessive sodium intake (HR of 1.6). Farez et al 7 reported incidence rate ratios of more than 2.5 and 3.3 for patients with medium and high sodium intake compared to those with low sodium intake, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Obesity in childhood or at 20 years of age has been confirmed as a risk factor in a cohort of 1235 adult MS patients [109], and further increases the risk in patients with previous EBV infection [110] and carrying the HLA-DRB1*15 allele [111]. Diet has been investigated as a possible risk factor: in this context the role of salt-intake has been investigated in a recent publication, but no correlation was found [112].…”
Section: Mri: a True Distinctive Pattern In Ped-ms?mentioning
confidence: 99%